2015
DOI: 10.2903/j.efsa.2015.3988
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the pest categorisation of Circulifer haematoceps and C. tenellus

Abstract: The Panel on Plant Health performed a pest categorisation of Circulifer tenellus (Ct) and C. haematoceps (Ch) (Hemiptera, Cicadellidae) for the European Union (EU) territory. They are well-defined insect species that can be identified on the basis of external morphology and male genitalia. Ch and Ct are considered to originate from the Old World; Ct is also present in North America and the Caribbean. In the EU, Ch is reported in 11 Member States, mostly in southern or central Europe, and Ct is reported in Spai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Seasonal dispersals can occur over relatively long distances. In the USA reports have shown that C. tenellus can migrate from the desert in Utah were it breeds, to invade distant sugar beet crops that are up to 300 km away (EFSA PLH Panel, 2015). Similar migration patterns and distances have been described for C. tenellus in the southwestern part of the USA or from northern Mexico to Miami, Florida (Severin, 1933;Dorst and Davis, 1937).…”
Section: Insect Vectors For Bctv and Their Distribution In The Eumentioning
confidence: 69%
See 1 more Smart Citation
“…Seasonal dispersals can occur over relatively long distances. In the USA reports have shown that C. tenellus can migrate from the desert in Utah were it breeds, to invade distant sugar beet crops that are up to 300 km away (EFSA PLH Panel, 2015). Similar migration patterns and distances have been described for C. tenellus in the southwestern part of the USA or from northern Mexico to Miami, Florida (Severin, 1933;Dorst and Davis, 1937).…”
Section: Insect Vectors For Bctv and Their Distribution In The Eumentioning
confidence: 69%
“…Consequently, outside the natural range of the vector, BCTV infected plants may occur but without further spread of the virus from its source. As explained in the 'Scientific Opinion on pest categorisation of C. haematoceps and C. tenellus' (EFSA PLH Panel, 2015), it is possible that C. tenellus is already present (but not reported) in few EU countries, such as Portugal, Slovenia and Croatia, and if still absent from these countries, it could spread into presently uncolonised areas where ecoclimatic conditions are suitable for its development.…”
Section: Vectors and Their Distribution In The Eu (If Applicable)mentioning
confidence: 99%